FENOMENA DAKWAH DI TELEVISI (KAJIAN DALAM DUNIA INFOTAINMENT) - Abdul Wahid (Fakultas Dakwah dan Komunikasi, 2015)
Media is a tool used in marketing the products of capitalist society culture and create a lifestyle materialistic, pragmatic, hedonist and consumerist even. Although on the other hand the presence of the media to bring a positive influence in digging the ideas of human thought that can support the formation of critical mass. One program or event that is very loved by society today is that many infotainments publish personal lives and careers of celebrities. Therefore, it is a tremendous business advantage, even will be aired every day because mumpung public interest. While morality is an event impressed ignored. Among the negative effects of infotainment serving them is, tends to accustom the public to see the mistakes of others, and spent a lot of time audience (people). Propaganda strategy in balancing the infotainment program include; made the Prophet. as a role model as a whole, delivering propaganda through mass media, especially television and unearth the religious teachings in everyday life with consistent and istiqamah.